Does the ECB policy of quantitative easing impact environmental policy objectives?. Issue 3 (3rd July 2022) - Hilmi, Nathalie; Djoundourian, Salpie; Shahin, Wassim; Safa, Alain
ABSTRACT: The relationship between the environment and climate change on one hand and the financial system, financial regulation and monetary policy on the other is growing in importance. This paper examines the possible impact of the European Central Bank's monetary policy of quantitative easing on the environmental policy of the European Union. Using data from Climate Bonds Initiative, the paper analyses the variation in the amount of "green labelled bonds" issued in the individual member countries of the Eurozone areas, as a function of liquidity inducing monetary policy variables. The paper finds a positive and significant relationship between the two measures.